Spin-3/2 and spin-2 charged massive states in a constant electromagnetic background - Benakli, Karim; Daniel, Cassiano A. [UNESP]; Ke, Wenqi (Springer Nature, 2023)
We develop in components the superspace action obtained in [1] describing the first massive level of the open charged superstring in a flat four-dimensional spacetime. In the absence of an electromagnetic background, we show how the Rarita-Schwinger and Fierz-Pauli Lagrangians are retrieved for spin-3/2 and 2, respectively. We then write different forms of the action in the presence of the electromagnetic background. The resulting equations of motion describe the propagation of fields of charged spin-3/2 and spin-1/2 on the one hand, and spin-2, 1 and 0 on the other.
Keywords: Effective Field Theories; Superspaces; Supersymmetric Effective Theories; Supersymmetric Gauge Theory